Behavioral evidence for the role of cortical θ oscillations in determining auditory channel capacity for speech - Ghitza, Oded (Frontiers in Psychology, 2014)
Studies on the intelligibility of time-compressed speech have shown flawless performance for moderate compression factors, a sharp deterioration for compression factors above three, and an improved performance as a result of “repackaging”—a process of dividing the time-compressed waveform into fragments, called packets, and delivering the packets in a prescribed rate. This intricate pattern of performance reflects the reliability of the auditory system in processing speech streams with different information transfer rates; the knee-point of performance defines the auditory channel capacity. This study is concerned with the cortical computation principle that determines channel capacity. Oscillation-based models of speech perception hypothesize that the speech decoding process is guided by a cascade of oscillations with theta as “master,” capable of tracking the input rhythm, with the theta cycles aligned with the intervocalic speech fragments termed θ-syllables; intelligibility remains high as long as theta is in sync with the input, and it sharply deteriorates once theta is out of sync. In the study described here the hypothesized role of theta was examined by measuring the auditory channel capacity of time-compressed speech undergone repackaging. For all speech speeds tested (with compression factors of up to eight), packaging rate at capacity equals 9 packets/s—aligned with the upper limit of cortical theta, θmax (about 9 Hz)—and the packet duration equals the duration of one uncompressed θ-syllable divided by the compression factor. The alignment of both the packaging rate and the packet duration with properties of cortical theta suggests that the auditory channel capacity is determined by theta. Irrespective of speech speed, the maximum information transfer rate through the auditory channel is the information in one uncompressed θ-syllable long speech fragment per one θmax cycle. Equivalently, the auditory channel capacity is 9 θ-syllables/s.